2013
DOI: 10.1182/blood-2012-08-451641
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1a enhances hematopoietic lineage commitment from human embryonic stem cells and inducible pluripotent stem cells

Abstract: Key Points• Expression of RUNX1a, an isoform of RUNX1, enhances blood cell production from human pluripotent stem cells.Advancements in human pluripotent stem cell (hPSC) research have potential to revolutionize therapeutic transplantation. It has been demonstrated that transcription factors may play key roles in regulating maintenance, expansion, and differentiation of hPSCs. In addition to its regulatory functions in hematopoiesis and blood-related disorders, the transcription factor RUNX1 is also required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 49 publications
1
95
1
3
Order By: Relevance
“…10,11 Enforced expression in murine hematopoietic cells enhances engraftment after transplantation. 12 Consistent with this, RUNX1a expands hematopoietic stem cells, 13,14 and dominant inhibition by RUNX1a results in monopoiesis. 15 Therefore, expression levels of each RUNX1 isoform are likely to be important for normal and malignant hematopoiesis.…”
Section: Introductionmentioning
confidence: 67%
“…10,11 Enforced expression in murine hematopoietic cells enhances engraftment after transplantation. 12 Consistent with this, RUNX1a expands hematopoietic stem cells, 13,14 and dominant inhibition by RUNX1a results in monopoiesis. 15 Therefore, expression levels of each RUNX1 isoform are likely to be important for normal and malignant hematopoiesis.…”
Section: Introductionmentioning
confidence: 67%
“…65,66 Previous attempts involving overexpression of single TFs, such as HOXB4, SCL, and RUNX1 in hPSCs have failed to yield durably engrafting cells. 26,67,68 A combination of HOXA9, ERG, and RORA endowed myeloid precursors with self-renewal capacity. The addition of SOX4 and MYB to this cocktail of TFs conferred engraftment potential with myeloid and erythroid lineages.…”
Section: Cd45mentioning
confidence: 99%
“…In humans, there are at least 12 different Runx1 mRNA isoforms that can be expressed in a cell-specific manner due to alternative splicing. Dr. Zhang found that forced expression of the Runx1a isoform in hPSCs promotes formation of definitive HSC-like cells that can expand ex vivo, engraft, and survive for at least 9 weeks after transplantation, giving rise to myeloid, lymphoid, and erythroid lineages [4]. While notable, these capabilities are not as robust as those observed for cord blood HSCs expressing Runx1a, indicating that expression of this single isoform is not sufficient to reverse all the deficiencies of PSC-derived HSCs.…”
Section: Intrinsic Hsc Programsmentioning
confidence: 99%